Reassessment of the Devonian problematicum Protonympha as another post‐Ediacaran vendobiont. (8th December 2017) - Retallack, Gregory J.
Abstract : Protonympha is an enigmatic fossil represented by two species from the Middle Devonian ( Protonympha transversa ) and Late Devonian ( Protonympha salicifolia ) of New York. Although interpreted in the past as a polychaete worm or starfish arm, Protonympha is not found with marine fossils, but with fossil plants. This fossil plant community was a swamp woodland of Lepidosigillaria whitei, with ground cover of Haskinsia colophylla, fringing brackish to freshwater coastal lagoons of the Catskill Delta. Protonympha shares with Ediacaran Vendobionta a quilted body of unskeletonized biopolymer that is unusually resistant to burial compaction. In overall form, Protonympha is most like the Ediacaran genus Spriggina . Protonympha has branching and tapering tubular structures radiating from the bottom. These rhizine‐like structures, thallus stratification and internal chambers revealed by petrographic thin sections suggest affinities with lichenized fungi. As for Cambrian Swartpuntia and Ordovician–Silurian Rutgersella, Protonympha may have been a post‐Ediacaran vendobiont.